The Spectrum of Cutaneous Manifestations in Lupus Erythematosus: The Tertiary Hospital Experience - Mowla, Mohammad Rafiqul; Alam, Mansurul; Hoque, Md Gofranul; Islam, AQM Serajul; Dey, Nishit Ranjan; Hoque, Roksana; Datta, Pradip Kumar; Hasan, Suzon Al (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: SLE; cutaneous; Chittagong DOI: 10.3329/jcmcta.v21i1.7668 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):34-39